Rapid Detection and Antibiotic Susceptibility of Uropathogenic Escherichia coli by Flow Cytometry - Alexandra Mihaela Velican; Luminiţa Măruţescu; Crina Kamerzan; Violeta Corina Cristea; Otilia Banu; Elvira Borcan; Mariana-Carmen Chifiriuc (Microorganisms, 2020)
Background: Early preliminary data on antibiotic resistance patterns available before starting the empiric therapy of urinary tract infections (UTIs) in patients with risk factors for acquiring antibiotic resistance could improve both clinical and epidemiological outcomes. The aim of the present study was two-fold: (i) to assess the antibiotic susceptibility of uropathogenic Escherichia coli isolates, exhibiting different antibiotic resistance phenotypes, directly in artificially contaminated urine samples using a flow cytometry (FC) based protocol; (ii) to optimize the protocol on urine samples deliberately contaminated with bacterial suspensions prepared from uropathogenic E. coli strains. Results: The results of the FC based antimicrobial susceptibility testing (AST) protocol were compared with the reference AST methods results (disk diffusion and broth microdilution) for establishing the sensitivity and specificity. The proposed FC protocol allowed the detection and quantification of uropathogenic E. coli strains susceptibility to nitrofurantoin, trimethoprim–sulfamethoxazole, ciprofloxacin, and ceftriaxone within 4 h after the inoculation of urine specimens. The early availability of preliminary antibiotic susceptibility results provided by direct analysis of clinical specimens could essentially contribute to a more targeted emergency therapy of UTIs in the anticipation of AST results obtained by reference methodology. Conclusions: This method will increase the therapeutic success rate and help to prevent the emergence and dissemination of drug resistant pathogens.